Biodiesel from moringa stenopetala seed oil (Bangladesh Journal of Scientific and Industrial Research, 2023)
The aim of this paper is the production and characterization of biodiesel from Moringa stenopetala seed oil. Biodiesel is a renewable, biodegradable, and nontoxic biofuel. Moringa stenopetala seed oil is a potential feedstock that has not been discovered as an energy source. This study investigated the effects of process parameters: methanol to oil ratio, reaction temperature, and catalyst loading on the yield and quality of biodiesel. The experimental results showed that the maximum biodiesel yield was 94% and it was obtained at optimum process conditions: temperature 55°C, methanol to oil ratio 6:1, and catalyst loading1.0. Biodiesel product was characterized based on international standards for testing fuels. According to the findings of the study, moringa stenopetala seed oil biodiesel has a specific gravity of 0.874 g/mole, a kinematic viscosity of 4.8 mm2/s, an acid value of 0.4 mg KOH/g, a saponification value of 196 mg KOH/g, FFA 0.2%, iodine value 104.5 high heating value 10,287 cal/g, flash Point 184°C, pour point 1°C, cloud point 10°C and cetane number 53. These results satisfy international standards for biodiesel.Bangladesh J. Sci. Ind. Res. 58(1), 35-44, 2023